Budaya Organisasi dalam Berbagi Pengetahuan Pustakawan Kementerian Sekretariat Negara Republik Indonesia - Widyarini, Meiryzka; Laksmi, Laksmi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2019)
This research discusses about the practice of knowledge sharing among librarians of the Ministry of State Secretariat Republic of Indonesia. This study aims to determine the implementation of knowledge sharing among librarians and analyze it through factors and the barriers that influence knowledge sharing. The factors that influence knowledge sharing between librarians such as nature of knowledge, work culture, motivation to share, opportunity to share and attitude of staff. The researcher employed a qualitative research design with a case study method. Data collection is through in-depth interviews, observation and analysis of documents that related to knowledge sharing in the Ministry of State Secretariat’s Library. The study findings revealed that the nature of knowledge consists of tacit and explicit. Related to motivation of librarians to share knowledge, there are two types of motivation extrinsic and intrinsic. Organizations provide opportunities to share knowledge in formal and informal, even though its still not become a systematic program. Meanwhile, staff attitude is the most dominant factor in influence knowledge sharing process among librarians. It was found by how senior librarians are willing to share the knowledge that they have with others. Furthermore, lack of management support was identified as a barrier because knowledge sharing still not become a culture of the organization.